S106 Influenza Infection of Human Lung Macrophages Increases PDL1 Expression. (19th November 2012) - Staples, KJ; Spalluto, CM; McKendry, RT; Wilkinson, TMA
Abstract : Background & Objective: Influenza infection has recently been shown to cause rapid functional impairment of CD8+ T cell responses in a murine infection model via the PD1/PDL1 pathway. 1 In this mouse model, it was the induction of PDL1 that was required for this impairment of CD8+ function. A previous study suggested that the anti-inflammatory cytokine, IL-10, was the principal driver of human macrophage PDL1 expression in response to HIV infection. 2 The aim of this study was to investigate how human lung macrophages regulate their PDL1 expression in response to influenza infection. Methods: Alveolar macrophages washed from resected human lung tissue and purified by plate adherence or human positively-isolated CD14+ monocyte-derived macrophages (MDMs) were cultured with H3N2 X31 influenza virus or a UV-irradiated aliquot of virus (UVX31) for 2 h, after which the cultures were washed and media replaced and incubation continued for a further 22 h. Virally infected cells and expression of cell surface markers were identified using flow cytometry. Gene expression was measured using RT-PCR. Results: No increase in MDM infection was seen using the UVX31 but incubation with X31 resulted in an average infection rate of 9.1%. Infection with X31 significantly increased cell surface expression of HLA-DR and PDL1 (p<0.05), but not of PDL2 by MDMs as measured by flow cytometry. Using RT-PCR, we observed an increase of PDL1 mRNA after X31 infection suggesting that the expression of this protein is transcriptionally regulated. In addition, we saw an increase in type I interferon expression by MDMs in response to X31 infection, but no expression of IFNγ. In contrast we observed a trend towards decreased expression of IL-10 mRNA. In further experiments, infection of alveolar macrophages with X31 also caused significant increases in HLA-DR and PDL1 cell surface expression. Conclusions: These data indicate that, in contrast to HIV infection of macrophages2 influenza-induced expression of PDL1 may not be regulated by IL-10 in human macrophages. Erickson et al (2012) J Clin Invest doi: 10.1172/JCI62860. Rodriguez-Garcia, et al. (2011) J Leukoc Biol 89(4):507–15.